JOB BURNOUT (BURNOUT) WITH PERFORMANCE BY NURSES IN NURSING CARE PROVISION - Triyoga, Akde; Maharani, Puspa Ayu (Jurnal Penelitian STIKES Kediri, 2012)
Job burnout is a condition that physical, emotional and mental drop caused by a very demanding job situation in the long term. This study aims to determine the job burnout relationship with the performance of nurses in providing nursing care in Inpatient Installation Kediri Baptist Hospital. Design used in this study were Analytical Correlation. The populations were nurses who worked in Inpatient Installation Kediri Baptist Hospital. The number of samples were 53 respondents and was taken by Accidental Sampling. Independent variable is job burnout and the dependent variable is the performance of nurses. Data was collected using questionnaires and observations, then analyse using Spearman's rho test with a significance level of Ï> 0.05. These results indicate that most respondents experienced light job burnout as many as 45 respondents (85%), and the majority of respondents have a performance in the provision of good nursing care that was 39 respondents (73.6%). The results of statistical spearman's rho tests showed Ï = 0068. The conclusion of this study is no relationship of job burnout with the performance of nurses in providing nursing care at inpatient installation Kediri Baptist Hospital.